Pharmacokinetic and behavioural profile of THC, CBD, and THC+CBD combination after pulmonary, oral, and subcutaneous administration in rats and confirmation of conversion in vivo of CBD to THC - Hložek, Tomáš; Uttl, Libor; Kadeřábek, Lukáš; Balíková, Marie; Lhotková, Eva; Horsley, Rachel R.; Nováková, Pavlína; Šíchová, Klára; Štefková, Kristýna; Tylš, Filip; Kuchař, Martin; Páleníček, Tomáš (European neuropsychopharmacology, 2017)
Metabolic and behavioural effects of, and interactions between Δ9-tetrahydrocannabinol (THC) and cannabidiol (CBD) are influenced by dose and administration route. Therefore we investigated, in Wistar rats, effects of pulmonary, oral and subcutaneous (sc.) THC, CBD and THC+CBD. Concentrations of THC, its metabolites 11-OH-THC and THC-COOH, and CBD in serum and brain were determined over 24h, locomotor activity (open field) and sensorimotor gating (prepulse inhibition, PPI) were also evaluated. In line with recent knowledge we expected metabolic and behavioural interactions between THC and CBD. While cannabinoid serum and brain levels rapidly peaked and diminished after pulmonary administration, sc. and oral administration produced long-lasting levels of cannabinoids with oral reaching the highest brain levels. Except pulmonary administration, CBD inhibited THC metabolism resulting in higher serum/brain levels of THC. Importantly, following sc. and oral CBD alone treatments, THC was also detected in serum and brain. S.c. cannabinoids caused hypolocomotion, oral treatments containing THC almost complete immobility. In contrast, oral CBD produced mild hyperlocomotion. CBD disrupted, and THC tended to disrupt PPI, however their combination did not. In conclusion, oral administration yielded the most pronounced behavioural effects which corresponded to the highest brain levels of cannabinoids. Even though CBD potently inhibited THC metabolism after oral and sc. administration, unexpectedly it had minimal impact on THC-induced behaviour. Of central importance was the novel finding that THC can be detected in serum and brain after administration of CBD alone which, if confirmed in humans and given the increasing medical use of CBD-only products, might have important legal and forensic ramifications.